Prospective memory in students with learning disabilities - Alotaibi Razaan M. (Univerzitet u Beogradu - Fakultet za specijalnu edukaciju i rehabilitaciju, 2021)
Introduction. The importance of memory is not restricted to remembering the knowledge and experiences of the past retrospective memory (RM), but also to remember what an individual must accomplish in the future prospective memory (PM). Objectives. The aim of this study was to identify RM and PM levels in students with learning disabilities (LD) according to some variables (gender, grade) and to identify the differences between the two types of memories. Methods. The study followed the comparative descriptive statistics. The study sample consisted of 37 male and female students with LD in middle school. The Prospective and Retrospective Memory Questionnaire (PRMQ) was used in this study. Results. The results include the following: a statistically significant decrease from the average in PM and RM levels in students with LD, the existence of statistically significant differences between PM and RM in students with LD for the RM, the presence of statistically significant differences in the PM and RM according to the gender variable for females, and the presence of statistically significant differences in PM and RM according to the grade variable for the third grade of middle school. Conclusion. Students with LD may suffer from a decrease in their capacity to remember in the future, which causes many difficulties in daily life. We guide teachers to use external AIDS for students with LD (such as writing notes) to help students remember performing their tasks.